1997
DOI: 10.1002/(sici)1096-9063(199710)51:2<171::aid-ps612>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of barnyardgrass (Echinochloa crus-galli) to atrazine and quinclorac

Abstract: : Two populations of Echinochloa crus-galli (R and I) exhibited resistance to quinclorac. Another population (X) exhibited resistance to quinclorac and atrazine. The R and I populations were collected from monocultures of rice in southern Spain. The X population was collected from maize Ðelds subjected to the application of atrazine over several years. The susceptible (S) population of the same genus was collected from locations which had never been treated with herbicides. The quinclorac value (dose causing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
2
34
0
7
Order By: Relevance
“…Em soja, o 2,4-D numa concentração de 100 ppm causou inibição da atividade fotossintética (Wedding et al, 1954). Wong (2000) também verificou redução de até 80% da taxa fotossintética de algas quando tratadas com 2 mg L -1 de 2,4-D. Lopez-Martinez et al (1997), trabalhando com biótipos resistentes de Echinochloa crus-galli, não observaram alterações no aparato fotossintético das plantas tratadas com quinclorac -herbicida que apresenta mesmo mecanismo de ação do picloram.…”
Section: Resultsunclassified
“…Em soja, o 2,4-D numa concentração de 100 ppm causou inibição da atividade fotossintética (Wedding et al, 1954). Wong (2000) também verificou redução de até 80% da taxa fotossintética de algas quando tratadas com 2 mg L -1 de 2,4-D. Lopez-Martinez et al (1997), trabalhando com biótipos resistentes de Echinochloa crus-galli, não observaram alterações no aparato fotossintético das plantas tratadas com quinclorac -herbicida que apresenta mesmo mecanismo de ação do picloram.…”
Section: Resultsunclassified
“…O controle das espécies desse gênero, em lavouras de arroz irrigado, tornou-se prática obrigatória, e geralmente é realizado com herbicidas aplicados em pré ou pós-emergência dessas plantas daninhas ou da cultura (Lopez-Martinez et al, 1997;Concenço et al, 2009;Galon & Agostinetto, 2009). O elevado uso de herbicidas para o controle de plantas daninhas, em arroz irrigado, deve-se à praticidade, à alta eficiência e, principalmente, à dificuldade de uso de outros métodos de controle após a inundação da lavoura, em que se Pesq.…”
Section: Introductionunclassified
“…Os efeitos negativos da infestação do capim-arroz na cultura podem ser atribuídos à alta capacidade de competição com as plantas de arroz por recursos limitantes do meio, à dificuldade de controle, ao aumento do custo de produção, ao acamamento das plantas da cultura, à dificuldade de colheita, à depreciação da qualidade do produto, à hospedagem de pragas, à redução do valor comercial das áreas cultivadas e ao surgimento da resistência a herbicidas (Lopez-Martinez et al, 1997;Andres et al, 2007;Concenço et al, 2009;Galon & Agostinetto, 2009).…”
Section: Introductionunclassified
“…On the other hand, for the control of three populations of quinclorac-resistant Echinochloa crusgalli found in Spain, herbicide doses up to 6, 10, and 26 times higher than the susceptible biotype used as reference were necessary for a 50% mass accumulation reduction (López-Martínez et al, 1997). Abdallah et al (2006), found a higher capacity of cyanide detoxification in the resistant biotype Digitaria ischaemum, with intensified production under quinclorac application.…”
Section: Introductionmentioning
confidence: 99%